FAKTOR PENGARUH BAURAN PEMASARAN PRODUK SASA INTI, BIO MIWON, DAN AJINOMOTO DALAM MENINGKATKAN PANGSA PASAR PRODUK PENYEDAP MAKANAN DI KOTA JEMBER - Dian Nasrullah; Sudaryanto Sudaryanto (STIE Mandala Jember, 2015)
The purpose of this study was to analyze the effect of product, distribution, pricing, promotion, sales personnel, procedures, services sales, promotion, the market share of food flavoring in Jember city. This study design was an explanatory research. The experiment was conducted in December - January 2014. Location of research conducted at City of Jember includes District Kaliwates, Patrang, and Sumbersari. The population in this study is a flavor enhancer product customers in the city of Jember. The study sample as many as 105 people. Methods of data analysis using logistic multinomial. Product variables significantly influence the consumer market flavoring Biomiwon over 1,848 times compared with Sasa. The results showed that the distribution of the variables do not significantly influence the trend of consumer market share Biomiwon flavor of 1.103 times compared with Sasa. Variable rates do not significantly influence the trend of consumer market share for flavoring Biomiwon 1,230 times compared with Sasa. Promotion variables significantly influence the trend of consumer market share Biomiwon flavor of 0.760 times compared with Sasa process variables significantly influence the trend of consumer market share for flavoring Biomiwon 1,830 times compared to Sasa promotion variables significantly influence the trend of consumer market share for 0.460 flavoring Biomiwon times compared with Sasa .